Optical Field Confinement Enhanced Single ZnO Microrod UV Photodetector - 魏铭 徐春祥 秦飞飞 Arumugam Gowri Manohari 卢俊峰 祝秋香 (Chinese physics letters, 2017)
ZnO microrods are synthesized using the vapor phase transport method, and the magnetron sputtering is used to decorate the A1 nanoparticles （NPs） on a single ZnO microrod. The micro-PL and I-V responses are measured before and after the decoration orAl NPs. The FDTD stimulation is also carried out to demonstrate the optical field distribution around the decoration of Al NPs on the surface of a ZnO microrod. Due to an implementation of AI NPs, the ZnO microrod exhibits an improved photoresponse behavior. In addition, AI NPs induced localized surface plasmons （LSPs） as well as improved optical field confinement can be ascribed to an enhancement of ultraviolet （UV） response. This research provides a method for improving the responsivity of photodetectors.